ANALISIS DEWATERING SYSTEM DALAM TAMBANG EMAS BAWAH TANAH - A.A Inung Arie Adnyano; Achmanda Belvadi Sahmin Pane (KURVATEK, 2020)
Underground mining location Ciurug L.450 south, there is a lot of water entering or stagnant in the mine opening hole. At Ciurug L.450 south there are 10 mine sumps. The pumping system flows from one mine sump to the next mine sump to the main mine sump. The pump is used 24 units and is used interchangeably because electricity is limited and one pump works 15 hours / day. The purpose of this study is to reduce the number of pumps that do not work optimally and the use of electric power. Groundwater discharge measurements were carried out manually in three locations namely Ramp Down A, Ramp Down B, and Ramp Down C using trenches. Based on observations and data analysis, groundwater discharge XC 445 2,899 (m3 / m), XC 438 B 8,940 (m3 / m), and XC 438 A 1,440 (m3 / m). The actual electricity consumption of 1561,7 Kw was reduced after being designed to be 1061.5 Kw, and a design 19 pumps units was used.Keywords: Flow System, Pump, Water Discharge